An antibody–supermolecule conjugate for tumor-specific targeting of tumoricidal methylated β-cyclodextrin-threaded polyrotaxanes. Issue 31 (23rd June 2020) - Nishida, Kei; Tamura, Astushi; Kang, Tae Woong; Masuda, Hiroki; Yui, Nobuhiko
Abstract : A conjugate of an anti-HER2 antibody and polyrotaxane containing methylated β-cyclodextrins (Me-PRX) was designed to achieve a tumor-specific delivery of Me-PRX. The antibody–Me-PRX conjugates efficiently uptaken into HER2-positive cells and induced autophagic cell death. Abstract : We previously found that acid-labile polyrotaxane containing methylated β-cyclodextrin (Me-PRX) induces endoplasmic reticulum (ER) stress-related autophagy and autophagic cell death. Me-PRX-induced autophagic cell death occurs even in apoptosis-resistant cells; tumor-targeted Me-PRX delivery could thus be an effective cancer treatment approach. In this study, antibody–supermolecule conjugates, consisting of a tumor-specific antibody and Me-PRX, were designed to achieve a tumor-specific delivery of Me-PRX. Trastuzumab, a monoclonal antibody against HER2 expressed in various malignant tumors, was selected as a tumor-targeting antibody, and phenyl maleimide group-modified Me-PRX (Mal-Me-PRX) was conjugated to the cysteine residue of the reduced Trastuzumab to obtain a Trastuzumab–Me-PRX conjugate (Tras-Me-PRX). The cellular association of Tras-Me-PRX to HER2-expressing tumor cells was remarkably greater than that of unmodified Me-PRX. Moreover, Tras-Me-PRX effectively reduced the viability of HER2-expressing tumor cells at a lower concentration compared to the unmodified Me-PRX. In conclusion, antibody–Me-PRX conjugates are regarded as a new class of antibody–drug conjugates that would contribute to the chemotherapy of cancers.